An examination of the size effect in quasi-brittle materials using a bond-based peridynamic model. (1st July 2022) - Hobbs, Mark; Dodwell, Tim; Hattori, Gabriel; Orr, John
Abstract: This paper examines the size effect in quasi-brittle materials using a three-dimensional bond-based peridynamic model. This is the first time that the capability of a peridynamic model to capture the size effect in quasi-brittle materials has been examined. Correctly reproducing the size effect is an essential check on the validity of any computational model and it is demonstrated that a bond-based peridynamic model can accurately capture the failure stress of geometrically identical structures over a range of sizes. A systematic examination of geometrically similar notched and unnotched beams provides new insights into the predictive capabilities of the model, and mode I and mixed-mode problems are considered to examine the generality of the model. The model is validated using published experimental data, and the predictive accuracy is equivalent, if not superior, to well-established numerical methods whilst offering several benefits that justify further research and development. This study provides evidence that the length scale in a peridynamic model is a numerical parameter and not a material property. Highlights: This is the first work to examine the structural size effect using a peridynamic model. A bond-based peridynamic model can accurately capture the deterministic size effect. Numerical results are in good agreement with published experimental data. This work provides an important check on the validity of the peridynamic model. The non-local length scale is a numerical parameter, not a material property.